Computational and in vitro Pharmacodynamics Characterization of 1A-116 Rac1 Inhibitor: Relevance of Trp56 in Its Biological Activity - González, Nazareno; Cardama, Georgina A.; Chinestrad, Patricio; Robles-Valero, Javier; Rodríguez-Fdez, Sonia; Lorenzo-Martín, L. Francisco; Bustelo, Xosé R.; Lorenzano Menna, Pablo; Gomez, Daniel E. (Frontiers in Cell and Developmental Biology, 2020)
In the last years, the development of new drugs in oncology has evolved notably. In particular, drug development has shifted from empirical screening of active cytotoxic compounds to molecularly-targeted drugs blocking specific biologic pathways that drive cancer progression and metastasis. Using a rational design approach, our group has developed 1A-116 as a promising Rac1 inhibitor, with antitumoral and antimetastatic effects in several types of cancer. Rac1 is over activated in a wide range of tumor types and it is the most studied protein of the Rho GTPase family. Its role in actin cytoskeleton reorganization has effects on endocytosis, vesicular trafficking, cell cycle progression and cellular migration. In this context, the regulatory activity of Rac1 affects several key processes of the course of the cancer disease, such as invasion and metastasis. The purpose of this preclinical study was to emphasize on the mode of action of 1A-116, conducting an interdisciplinary approach with in silico bioinformatics tools and in vitro assays. Here, we demonstrate that 1A-116 interferes with protein-protein interactions of Rac1 with several GEFs activators and that the tryptophan 56 residue of Rac1 is necessary for the inhibitory effects of 1A-116. 1A-116 is also able of inhibiting the oncogenic Rac1P29S mutant protein, one of the oncogenic drivers found in sun-exposed melanoma. It also inhibits numerous Rac1-regulated cellular processes such as membrane ruffling and lamellipodia formation. These results deepen our knowledge of 1A-116 inhibition of Rac1 and its biological impact on cancer progression. They also represent a good example of how in silico analyses represent a valuable approach for drug development.